Ethnic and Sex Diversity in Academic Orthopaedic Surgery: A Cross-sectional Study. (8th March 2022) - Vij, Neeraj; Singleton, Ian; Bisht, Roy; Lucio, Francisco; Poon, Selina; Belthur, Mohan V.
Abstract : Introduction: Although the diversity in orthopaedic residency programs has been studied, the diversity within academic orthopaedics has not. Methods: The board of specialty societies, five leading journals and the National Institutes of Health RePORTER tool, and three accreditation organizations were explored. Results: The board of directors comprised 220 (72%) Caucasians, 36 (12%) Asians, 4 (1%) Hispanic/Latinos, 29 (9%) African Americans, and 18 (6%) Other individuals; 250 (81%) were men, and 57 (19%) were women. The editorial boards comprised 288 (77%) Caucasians, 62 (16%) Asians, 14 (4%) Hispanic/Latinos, 8 (2%) African Americans, and 4 (1%) Other individuals; 341 (91%) were men, and 35 (9%) were women. The National Institutes of Health grant recipients comprised 117 (64%) Caucasians, 58 (32%) Asians, 4 (2%) Hispanic/Latinos, and 3 (2%) African Americans; 128 (70%) were men, and 54 (30%) were women. On average, Caucasians, Asians, Hispanic/Latinos, and African Americans received $776, 543, $439, 600, $420, 182, and $494, 049, respectively. On average, men and women received $759, 426 and $419, 518, respectively. The accreditation boards comprised 45 (82%) Caucasians, 6 (11%) Asians, and 4 (7%) African Americans; 45 (82%) were men, and 10 (18%) were women. Conclusions: Academic orthopaedic surgery does not resemble the United States. Residency, fellowship committees, and professional organization boards need to become aware of these disparities.